2021
DOI: 10.1177/2333794x21990340
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pediatric Emergency and Risk Factors for Life-saving Interventions

Abstract: Pediatric emergency patients are vulnerable population and require special care or interventions. Nevertheless, there is limited data on the prevalence and risk factors for life-saving interventions. This study is a retrospective analytical study. The inclusion criteria were children aged 15 years or under who were triaged as level 1 or 2 and treated at the resuscitation room. Factors associated with LSI were executed by logistic regression analysis. During the study period, there were 22 759 ER visits by 14 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Berdasarkan kategori usia, mayoritas pasien anak yang berkunjung ke ruang gawat darurat berusia 1-5 bulan. Penelitian lain oleh Seo dkk, 11 Phattharapornjaroen dkk, 16 Brugnolaro dkk, 7 Jofiro dkk, 8 Dharmawati dkk 4 juga melaporkan bahwa pasien berusia 1-5 tahun diamati lebih banyak melakukan kunjungan ke ruang gawat darurat anak. Hasil penelitian ini sejalan dengan penelitian yang dilakukan Riva dkk 14 bahwa anak usia 10-24 bulan dengan puncak usia 1 tahun berkontribusi besar terhadap jumlah kunjungan gawat darurat (46,7%).Penelitian Akbayram dkk 15 juga melaporkan hasil serupa bahwa pasien usia <5 tahun merupakan kelompok usia yang paling banyak ditemui pada ruang gawat darurat anak.…”
Section: Pembahasanunclassified
“…Berdasarkan kategori usia, mayoritas pasien anak yang berkunjung ke ruang gawat darurat berusia 1-5 bulan. Penelitian lain oleh Seo dkk, 11 Phattharapornjaroen dkk, 16 Brugnolaro dkk, 7 Jofiro dkk, 8 Dharmawati dkk 4 juga melaporkan bahwa pasien berusia 1-5 tahun diamati lebih banyak melakukan kunjungan ke ruang gawat darurat anak. Hasil penelitian ini sejalan dengan penelitian yang dilakukan Riva dkk 14 bahwa anak usia 10-24 bulan dengan puncak usia 1 tahun berkontribusi besar terhadap jumlah kunjungan gawat darurat (46,7%).Penelitian Akbayram dkk 15 juga melaporkan hasil serupa bahwa pasien usia <5 tahun merupakan kelompok usia yang paling banyak ditemui pada ruang gawat darurat anak.…”
Section: Pembahasanunclassified
“…1 It was reported that 80% of child deaths occur due to emergency medical problems. 2 Pediatric patients are vulnerable and require special care or intervention techniques given their different anatomical, physiological and psychological structure than adults, 3,4 which renders the interventions concerning pediatric patients an intense, stressful and challenging process. 5 According to a report published in the U.S., 17% of all children in the U.S. apply to emergency care at least once, primarily due to fever, cough, nausea, vomiting, abdominal pain, as well as injuries, sprains, viral and respiratory tract infections.…”
Section: Introductionmentioning
confidence: 99%